"Doesn't Everyone Want That? It's Just a Given": Swedish Emerging Adults' Expectations on Future Parenthood and Work/Family Priorities. (January 2014) - Frisén, Ann; Carlsson, Johanna; Wängqvist, Maria
This study investigated Swedish emerging adults' expectations on future parenthood through interviews with 124 Swedish emerging adults who were not yet parents. Thematic analysis showed that most participants were sure they wanted to become parents, but not right now. First, they wanted a stable financial situation, a romantic relationship, and time for self-focus. More women than men talked about parenthood as a social norm and wanted to prioritize both work and family. More men than women wanted to prioritize either work or family before the other. The study showed that Swedish emerging adults postpone, but do not reject, parenthood and that gender differences in expectations on parenthood may contribute to a reproduction of gender inequalities in family life.